Assessment of the Performance of Membranes Type Koch in Hartha Power Plant - Ala'a Abdulrazaq Jassim (International Journal of Chemical Engineering)
This paper deals with the assessment of the performance of reverse osmosis membranes type (TFC-Koch) model (8822XR-365) which are used in water desalination unit in Hartha power plant, one of the electrical power plant in the south Iraq. This unit has a capacity of 100 m3/h withdraws water from Shat Al-Arab River as a raw water having total dissolved solid (TDS) >3000 ppm, and consists of two stages with total recovery and salt rejection of about 60% and 95%, respectively. The first array contains twelve vessels and the second six vessels. Each vessel contains six elements, 8 inches in diameter and 40 inches in length. The performance of the reverse osmosis (RO) membranes is based on surveying the chemical analysis of different ions present in water for both permeate and rejected streams from the unit log book, and only those readings where the overall recovery was 60% were selected. The results depicted that the reduction of membrane efficiency is attributed to the membrane blockage due to scaling and fouling. Under high fouling conditions the permeate flow rate is reduced and accordingly a high feed pressure is required to produce the design flow rate of permeate or percent recovery. A simulation of the behavior of RO membranes was conducted using standard Saehane software and compared with predicted model that was developed by the same authors. The results revealed that the reduction in water flow in both elements one and two in each vessel in the first array is attributed to the high permeate water flux through these two elements beyond the operation limits. Accordingly it is necessary to replace these two elements or change their position relative to other elements periodically.